Affective memory and reconstruction of a pioneer FM radio station in Brazil - Kischinhevsky, Marcelo; Rêgo Henriques, Pedro (InMediaciones de la Comunicación, 2016)
This article seeks to investigate the strategies to build a collective affective memory and the brand (re) construction of a FM musical radio-station. The case study is conducted about the relaunch of Rádio Cidade, after eight years out of the dial in Rio de Janeiro, Brazil. Launched in 1977, Rádio Cidade was a pioneer in building a young and irreverent language then being identified, in its first decades of existence, as a radio-station that configured the hit radio segment in the Brazilian market of radio broadcasting. Emitting exclusively over the internet since 2006, Rádio Cidade returned to the air on hertzian-waves in 2014, trying to reinvent itself as radio rock, in a complex enunciative approach. (Complete article in portuguese language).